2023
DOI: 10.3390/ijms24065369
|View full text |Cite
|
Sign up to set email alerts
|

Proanthocyanidins: Impact on Gut Microbiota and Intestinal Action Mechanisms in the Prevention and Treatment of Metabolic Syndrome

Abstract: The metabolic syndrome (MS) is a cluster of risk factors, such as central obesity, hyperglycemia, dyslipidemia, and arterial hypertension, which increase the probability of causing premature mortality. The consumption of high-fat diets (HFD) is a major driver of the rising incidence of MS. In fact, the altered interplay between HFD, microbiome, and the intestinal barrier is being considered as a possible origin of MS. Consumption of proanthocyanidins (PAs) has a beneficial effect against the metabolic disturba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 133 publications
0
1
0
Order By: Relevance
“…These data suggest that dietary Pro may prevent metabolic syndrome in the intestines of common carp. In addition, some studies have found that dysbiotic Proteobacteria expansion is associated with epithelial dysfunction and inflammation [83,84]. Our results showed a lower Proteobacteria abundance in the Pro group, suggesting that Pro may have potential effects against epithelial dysfunction and inflammation in intestines.…”
Section: The Effect Of Pros On Intestinal Microbiotasupporting
confidence: 59%
See 1 more Smart Citation
“…These data suggest that dietary Pro may prevent metabolic syndrome in the intestines of common carp. In addition, some studies have found that dysbiotic Proteobacteria expansion is associated with epithelial dysfunction and inflammation [83,84]. Our results showed a lower Proteobacteria abundance in the Pro group, suggesting that Pro may have potential effects against epithelial dysfunction and inflammation in intestines.…”
Section: The Effect Of Pros On Intestinal Microbiotasupporting
confidence: 59%
“…A marked reduction in the ratio of F/B was observed in ovariectomized mice after treatment with Pros (grape seed extract) [82]. Moreover, Pro treatment has been shown to alter the gut microbiota by increasing Bacteroidetes and decreasing Firmicutes, effectively alleviating metabolic syndrome induced by a high-fat diet (reviewed by Redondo-Castillejo, et al [83]). Consistent with previous findings, our data also revealed a significant decrease in Firmicutes abundance and a 2.35-fold increase (but p > 0.05) in Bacteroidota abundance in the Pro group.…”
Section: The Effect Of Pros On Intestinal Microbiotamentioning
confidence: 99%
“…It is also worth mentioning the role of gut microbiota in the prevention and treatment of MetS. A high-fat diet can contribute to MetS development by altering gut microbiota, while polyphenol intake can modulate its composition towards a healthy profile, having a beneficial impact against the metabolic disturbances in MetS [ 64 ]. In line with this, dietary patterns rich in fibers, such as a Mediterranean or a plant-based diet, in combination with polyphenol-rich juices, could provide a strategy to prevent and counteract MetS in humans [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…This includes in vitro and in vivo studies, as well as some clinical trials involving PAC supplementations from different sources (e.g., grape [15] , aronia berry [16] , blueberry [17] , avocado [18] ). These studies have consistently observed a stimulation of bifidobacteria and lactobacilli [19][20][21][22] . Moreover, Roseburia species and Faecalibacterium praustnitzii seem to flourish after PAC supplementation, while the response of Enterobacteriaceae is not consistent across studies [19,22] .…”
Section: Introductionmentioning
confidence: 82%
“…Moreover, Roseburia species and Faecalibacterium praustnitzii seem to flourish after PAC supplementation, while the response of Enterobacteriaceae is not consistent across studies [19,22] . PAC also favorably affect the bacteria Akkermansia muciniphila [19][20][21][22] . This bacterium is considered a next-generation probiotic and prefers the intestinal mucosal environment, where it can positively impact immunoprotection through stimulation of mucus turnover and enhancement of gut barrier function [17,[23][24][25] .…”
Section: Introductionmentioning
confidence: 99%